Analisis Yuridis Pemberian Upah Pemagangan Mahasiswa Ditinjau Dari Peraturan Menteri Ketenagakerjaan Nomor 6 Tahun 2020 Tentang Penyelenggaraan Pemagangan Di Dalam Negeri - Iftaatul Rizkiyah Maghfiroh; Ahmad Suryono (SS&H: Studies in Social Sciences and Humanities, 2024)
Impoving soft skills and hard skills in universities continoues to be persued, one of which is by launching an internship program for students. In its Implementation, the Regulation of the Minister of Manpower Number 6 of 2020 concerning the Implementation of Internship in the country states that interns have the right one of them in obtaining wages called pocket money. Therefore, this study aims to determine and analyze the legal protection, urgency and legal consequences of providing student internship wages in terms of the Minister of Manpower Regulation Number 6 of 2020 concerning the Implementation of Internships in the Country. This research is a normative law research conducted with data collection techniques, namely: literature studies, interviews, and documentation which are then analyzed qualitatively. Research results: first, internship students are not the subject of the Minister of Manpower Regulation Number 6 of 2020 concerning the implementation of internships in the country so that they are subject to the Civil Code based on the principle of freedom of contract, second, the legal urgency of providing internship wages to students does not have definite legal protection, so that student internships, especially the Independent Campus Learning Program, are included in vulnerable work and intervention is needed government due to the development of the student subject internship era is increasingly followed; Third, students enter a gray position with no clear regulations regarding the implementation of apprenticeships which results in not having the right to get pocket money or other rights according to regulations regarding internships.